Biomechanical Analysis of Cervical Artificial Disc Replacement Using Cervical Subtotal Discectomy Prosthesis - Wo, Jin; Lv, Zhenjing; Wang, Jing; Shen, Kui; Zhu, Haoran; Liu, Yang; Huang, Yuen; Sun, Guodong; Li, Zhizhong (Frontiers in Bioengineering and Biotechnology, 2021)
Anterior cervical discectomy and fusion (ACDF) is one of the standard treatments for degenerative disc disease. The treatment process sacrifices the segmental mobility, which can lead to increase adjacent intervertebral disc pressure and accelerate adjacent segment degeneration, and therefore increase the risk of reoperation. These challenges have promoted a motion-preserving cervical artificial disc replacement (CADR) substitute for ACDF. Our study have designed the cervical subtotal discectomy prosthesis (CSDP), consisting of the cervical disc prosthesis structure (CDP-structure), cervical vertebra fixation structure (CVF-structure), link-structure, and locking screw, and aimed to facilitate motion control and reduce subsidence. The aim of this study was to assess the biomechanics of a CSDP by using finite element (FE) analysis, the friction-wear test, and non-human primates implantation study.In FE analysis, the ROM of the CSDP FE model was close to that of the intact FE model in operative and adjacent segments. At the operative segment, the CSDP in the error FE model increased ROM in flexion-extension, lateral bending, and axial rotation. The facet joint force changes were minimal in extension, lateral bending, and axial rotation loads in CSDP. In the friction-wear test, after 150-W movement simulation, both the CVF-link-junction and CDP-link-junction had slight wear, especially in simulated body fluids environments. In the CSDP non-human primate implantation study, no subsidence, dislocation, or loosening was observed. At 1 year after CSDP implantation, the CVF-structure was fused to the vertebral body. There was no spinal cord edema, degeneration of the adjacent intervertebral disc, or inflammation of the surrounding vertebral body observed on MRI. In FE analysis, the biomechanical parameters of the CSDP FE model were relatively close to those of the intact FE model when compared to the Prestige LP FE model. In terms of CSDP error FE models, we demonstrated that the implantation position influences CSDP performance, including ROM, bone-implant interface stress, and facet joint force. In addition, we performed a friction-wear test on the CSDP to assess its durability. Finally, CSDP studies in non-human primates have shown that the CSDP is effective.